Penyuluhan Manajemen Pemeliharaan Ternak Ruminansia Di Kelompok Ternak Desa Sukadana, Kecamatan Pujut, Kabupaten Lombok Tengah - Aminurrahman; Sulaiman Ngongu Depamede; Rr. Agustin; Dwi Kusuma Purnamasari; Zaid Al Gifari; Rezki Amalyadi; Ine Karni; I Gede Nano Septian; Fahrullah; Muhammad Muhsinin; Vebera Maslami; Azhary Noersidiq (Universitas Mataram, 2026)
Ruminant livestock management counselling has been provided to farmer groups in Sukadana Village to improve skills in beef cattle husbandry, housing, health, and reproduction. The success of animal husbandry depends on breeding, feeding, and rearing management, with non-genetic factors contributing greatly to reproductive efficiency. This service aims to evaluate the effectiveness of ruminant husbandry management counselling conducted at the Sukadana Village Livestock Group, Pujut District, Central Lombok Regency. Lack of knowledge of farmers in maintenance is a major challenge. Counselling and training play an important role in improving farmers' knowledge and supporting food security and sustainable agriculture (SDGs point 2). This community service activity was carried out through surveys, interviews, observations, material presentation, and discussions to increase livestock productivity in Sukadana Village. The results showed that the counselling provided succeeded in increasing the knowledge and skills of farmers in the aspect of maintenance management. Farmers who actively participated in the counselling showed significant improvements in more efficient and sustainable farming practices. In addition, the evaluation results also revealed that the extension helped overcome some of the problems faced by farmers, such as feed shortages and livestock diseases. In conclusion, extension services on ruminant livestock management in the Sukadana Village Livestock Group have had a positive impact on improving farmers' productivity and welfare. Recommendations for future extension services include increasing the frequency and variety of extension materials, as well as developing a more comprehensive training programme to address the specific needs of farmers in the area.